(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The role of selenium (Se) deficiency in the development of thyroid associated ophthalmopathy has been actively debated in the literature. The question is still debated in Ukraine due to the absence of data both on selenium deficiency in this country and blood selenium levels in Graves’ disease patients with autoimmune ophthalmopathology (AO). Purpose: To investigate blood selenium levels in Graves’ disease patients with AO. Materials and Methods: Fifty-seven Graves’ disease patients were included in the study. Of these, 44 had AO. Clinical severity of AO was classified using the NOSPECS. Of the 44 patients with AO, 16, 19 and 9 patients had class 2b, class 3a or 3b, and class 4a, respectively. All patients were euthyroids receiving antithyroid therapy (mean TSH level, 1.36 ± 0.4 mIU/L; reference TSH range, 0.4 mIU/L to 4.0 mIU/L). A Hitachi MPF-2A fluorescence spectrophotometer was used to determine blood selenium levels. A blood selenium level between 75 and 120 μg/l was considered normal, between 50 and 75 μg/l was moderate Se deficiency, and <200 μg/l considered severe Se deficiency. Results: Of the 57 patients of both groups, 31 (54%) were found to be severely selenium deficient. The mean blood selenium level in Graves’ disease patients with AO was 60.07±7.61 μg/l, i.e., substantially lower than the normal range. In addition, 34% of these patients had a normal blood selenium level, whereas 16% and 50%, moderate and severe Se deficiency, respectively. The mean blood selenium level in Graves’ disease patients without AO was 34.4±10.2 μg/l, i.e., also substantially lower than the normal range. In addition, 31% of these patients had a normal blood selenium level, whereas 69%, severe Se deficiency. Conclusion: First, irrespective of the presence or absence of AO, 54% of Graves’ disease patients were found to exhibit severe selenium deficiency. Second, the mean blood selenium level in Graves’ disease patients with AO was 60.07 ± 7.61 μg/l, and 50% of them exhibited severe selenium deficiency. In addition, the mean blood selenium level in patients with Graves’ disease only was 34.4 ± 10.2 μg/l, and 69% of them exhibited severe selenium deficiency. There was, however, no significant difference in blood selenium level between groups (Р > 0.05). Therefore, it may be assumed that selenium deficiency is not a factor affecting the development of AO in Graves’ disease. Finally, given that fact that 34% of Graves’ disease patients with AO exhibited no selenium deficiency, such patients should not be prescribed selenium agents without first checking their blood selenium levels.